Assessing the Use of Poly Aluminium Chloride Coated Granules From Water Treatment Sludge to Enhance the Dewatering of Fecal Sludge in Sludge Drying Beds - Sandra Akol (Uganda Christrian University, 2025)
Lubigi fecal sludge and waste water treatment plant is one of the main plant that manage the fecal sludge generated within Kampala. Despite the plant’s capacity to manage the fecal sludge generated, there is a high solid loading due to the incoming large volumes of waste beyond the design capacity and an additional long drying period of the sludge thus the need to optimum utilization of the drying beds. This study therefore aimed at assessing the use poly aluminium chloride coated granules from water treatment sludge to increase dewatering of fecal sludge within the fecal sludge drying beds. The raw fecal samples were obtained and analysed for pH, EC, moisture content and total solids, water treatment sludge was characterized using XRF to ensure that it was suitable for preparation of poly aluminium chloride of PH 3.78 and water treatment sludge granules. Water treatment sludge granules coated with poly aluminium chloride (PAC) exhibited potential in dewatering the fecal sludge, with the highest reduction in moisture content of 25.3% achieved in 28 days and 4g/l dose of water treatment sludge granule.
UNDERGRADUATE